Aligning perceptual and conceptual information for cognitive contextual system development : emerging research and opportunities - Kuvich, Gary, 1960- (Hershey, PA : IGI Global, 2018)
'This book address existing disconnect between the mainstream of machine perception, based on bottom-up mathematical models of features, and new results of applied cognitive science that allows for creating multilevel conceptual models, which provide context for driving perception top-down and deep understanding of perceived information by autonomous systems for fast and effective decision making'--
Includes bibliographical references (pages 147-149), and index.
Keywords: Artificial intelligence; Cognitive science; Automation; Perceptual learning